2023
DOI: 10.9734/ijecc/2023/v13i51768
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Micronutrients on Growth and Yield of Groundnut (Arachis hypogaea L.) Varieties

Abstract: During the summer season of 2022, a field experimental trail on groundnut was performed at Crop Research Farm (CRF), Department of Agronomy, SHUATS, Prayagraj (U.P.) to evaluate the impact of micronutrients on the growth and yield of groundnut (Arachis hypogea L.) varieties. The experimental plot's soil was sandy loam in texture, virtually neutral in soil reaction (pH 7.7), low in organic carbon (0.44%), available N (171.48 kg/ha), available P (27.00 kg/ha), and available K (291.20 kg/ha). The experiment was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
0
0
Order By: Relevance
“…TNAU groundnut-rich solution contains potassium which might improve the stomatal opening, resulting in an increased photosynthetic rate [ 41 ], and this was observed in the present study ( Table 10 ). Similarly, the application of inorganic fertilizers might have increased the availability of potassium, iron, magnesium and sulphur, resulting in increased chlorophyll content, photosynthetic rate, stomatal conductance, and transpiration rate [ 42 ], and a higher rate of translocation of photoassimilate from the source to its sink [ 43 ]. Chitdeshwari et al [ 44 ] demonstrated that in groundnut, the application of potassium during the flowering stage increased the number of flowers and pegs, and enhanced pod setting.…”
Section: Resultsmentioning
confidence: 99%
“…TNAU groundnut-rich solution contains potassium which might improve the stomatal opening, resulting in an increased photosynthetic rate [ 41 ], and this was observed in the present study ( Table 10 ). Similarly, the application of inorganic fertilizers might have increased the availability of potassium, iron, magnesium and sulphur, resulting in increased chlorophyll content, photosynthetic rate, stomatal conductance, and transpiration rate [ 42 ], and a higher rate of translocation of photoassimilate from the source to its sink [ 43 ]. Chitdeshwari et al [ 44 ] demonstrated that in groundnut, the application of potassium during the flowering stage increased the number of flowers and pegs, and enhanced pod setting.…”
Section: Resultsmentioning
confidence: 99%
“…Not only amount of nutrients present in soil but also their availability in meeting out needs of crop at critical growth stages resulted in increased plant growth and yield characters". Kamalakannan [14]; Elayaraja and Jawahar [8]; Kumar et al, [15].…”
Section: Yield Charactersmentioning
confidence: 99%